Difficulties in assessing the added value created by enterprises of the oil and gas sector of the Russian Federation - M. D. Khabib; P. N. Maksimov (Вестник университета)
The article considers the relevance of the problem of assessing the gross value added created by enterprises belonging to the oil and gas sector of the Russian Federation. There is no unified system of statistical indicators in the world that determine the boundaries and characterize the economy of the oil and gas complexes of the countries of the world. The World Bank’s calculation of the share of oil rents in the gross domestic product of the Russian Federation has adopted as one of the simple indicators for assessing the role of the oil and gas complex in the country’s economy. It has been noted that the oil rent is reflected only as a part of the primary income arising from the extraction of oil and gas, their processing, transportation and further use. The expediency of taking into account the entire value chain created in the oil and gas sector of the economy has been justified. The methodological difficulties of a number of interrelated problems have been highlighted in detail: measuring the added value created by service sector enterprises related to the oil and gas sector; complexly organization of production structures (vertically integrated companies); transfer pricing in the oil and gas industry; reflecting taxes and subsidies on products of the oil and gas sector. The conclusion has been made about the expediency of calculating the share of the oil and gas sector in the gross domestic product of the Russian Federation.